Karakteristik Campuran AC-WC Menggunakan Batu Sungai Sangtanete Dan Bahan Tambah Kantong Plastik - Fhiladelvia Tandiayu; Robert Mangontan; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The accumulation of plastic waste in Indonesia is increasing and will damage the environment around us if there is no proper handling. Therefore, to reduce the impact of the accumulation of plastic waste, a study was carried out to utilize the waste as an added material that can be used in the Laston AC-WC mixture, with the aim of knowing how the characteristics and effects of adding plastic waste in the pavement mixture using the conventional Marshall method and referring to Specifications of Highways 2018. The results obtained are stability values of 1757 kg, VIM 4.80%, flow 3.51 mm, VMA 16.18%, VFB 70.12%. All research results meet the specifications set by Bina Marga 2018.